Morfologia e sedimentação da praia do Marahú (lha de Mosqueiro/PA) - antes e após a construção de sua orla - PEREIRA, Yan Marcel Quadros (2022)
Mosqueiro Island (PA), belongs to the metropolitan region of Belém, is located in the estuary of Para River, with a coastline formed by a succession of promontories and sandy coves, which forms estuarine beaches that in recent decades have been greatly affected by the hydrodynamics of the river and the consequent coastal erosion, as is the case of Marahu beach, where erosion containment works were implemented to minimize the problem. The objective of this work was to analyze the morpho-sedimentary changes of Marahu beach before than after the construction of its edge with retaining wall. The study methodology was carried out by collecting sample data from the years 2016 to 2018; laboratory analysis; and treatments of topographic and sedimentological data. For the characterization of the morphodynamic state of the beach, morphometric parameter beach slope β was used, derived from the treatment of topographic data in 9 beach profiles, following the synthesis of Sazaki (1980) for beach classification. It is expected to obtain results on de chances that occurred on Marahu beach, after the construction of its edge, related to morphology, sedimentation and associated hydrodynamics hazards. It was observed that the beachs present a dissipative to reflective morphodynamics state and that the sediments vary from coarse to fine sand, being mostly medium sand, ranging from poorly sorted to well sorted. Before the construction of the edge and the retaining wall, the beach presented greater seasonal variation in its morphodynamic state. After the implementation of the work, the beach had more restricted sedimentary mobility, attenuating this variation. The work minimized the impacts of erosion. Works like this are important, as they generate information that can help alleviate socio-environmental problems, such as the indication of imminent losses of public and private heritage, due to coastal erosion, as well as to provide subsidies in the prediction of possible geological accidents associated with rainfall and fluvial in estuarine beachs of coves, located on the edge of coastal tablelands. Keywords: beach morphology; sedimentation; Marahú; estuarine beaches; Amazon.